2019
DOI: 10.2147/nss.s182158
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of traumatic brain injury on sleep: an overview</p>

Abstract: Traumatic brain injury (TBI) is a global health problem that affects millions of civilians, athletes, and military personnel yearly. Sleeping disorders are one of the underrecognized sequalae even though they affect 46% of individuals with TBI. After a mild TBI, 29% of patients have insomnia, 25% have sleep apnea, 28% have hypersomnia, and 4% have narcolepsy. The type of sleep disturbance may also vary according to the number of TBIs sustained. Diffuse axonal injury within the sleep regulation system, disrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…In the TBI population, sleep disturbances are common; occurring in nearly half of individuals, with effects lasting from months to years after the original injury and increasing with injury severity. 40-46 Similar relationships exist in individuals with persistent headaches 47,48 , and even chronic neck pain. 49 As such, it is not surprising that our results reflect that a combination of mTBI, headache, and neck pain produces a more severe phenotype than any given symptom in isolation.…”
Section: Discussionmentioning
confidence: 91%
“…In the TBI population, sleep disturbances are common; occurring in nearly half of individuals, with effects lasting from months to years after the original injury and increasing with injury severity. 40-46 Similar relationships exist in individuals with persistent headaches 47,48 , and even chronic neck pain. 49 As such, it is not surprising that our results reflect that a combination of mTBI, headache, and neck pain produces a more severe phenotype than any given symptom in isolation.…”
Section: Discussionmentioning
confidence: 91%
“…In the TBI population, sleep disturbances are common; occurring in nearly half of individuals, with effects lasting from months to years after the original injury and increasing with injury severity. [40][41][42][43][44][45][46] Similar relationships exist in individuals with persistent headaches 47,48 , and even chronic neck pain. 49 As such, it is not surprising that our results reflect that a combination of mTBI, headache, and neck pain produces a more severe phenotype than any given symptom in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Up to a third of the persons with acquired brain injury experience insomnia, which is defined as an inability to sleep, particularly associated with problems of falling asleep and maintaining sleep. [5][6][7] Since many studies did not diagnose sleep complaints as sleep disorders, this review focuses on sleep disturbances refering to sleep problems that occur at night and are characterized by the inability to initiate and maintain sleep. Several studies have reported a poorer sleep quality and a reduced sleep efficiency (ratio of time spent asleep compared with time spent in bed) due to more frequent awakenings at night.…”
Section: Introductionmentioning
confidence: 99%